Outcome of endoscopic vs microsurgical transsphenoidal resection for Cushing’s disease - Nidan Qiao (Endocrine Connections, 2018)
Introduction: It is unclear whether the proportions of remission and the recurrence rates differ between endoscopic transsphenoidal surgery (TS) and microscopic TS in Cushing’s disease (CD); thus, we conducted a systematic review and meta-analysis to evaluate studies of endoscopic TS and microscopic TS. Methods: We conducted a comprehensive search of PubMed to identify relevant studies. Remission and recurrence were used as outcome measures following surgical treatment of CD. Results: A total of 24 cohort studies involving 1670 adult patients were included in the comparison. Among these studies, 702 patients across 9 studies underwent endoscopic TS, and 968 patients across 15 studies underwent microscopic TS. Similar baseline characteristics were observed in both groups. There was no significant difference in remission between the two groups: 79.7% (95% CI: 73.1–85.0%) in the endoscopic group and 76.9% (95% CI: 71.3–81.6%) in the microscopic group (P = 0.485). It appears that patients who underwent endoscopic surgery experience recurrence less often than patients who underwent microscopic surgery, with recurrence proportions of 11.0% and 15.9%, respectively (P = 0.134). However, if follow-up time is taken into account, both groups had a recurrence rate of approximately 4% per person per year (95% CI: 3.1–5.4% and 3.6–5.1%, P = 0.651). Conclusions: We found that remission proportion and recurrence rate were the same in patients who underwent endoscopic TS as in patients who underwent microscopic TS. The definition of diagnosis, remission and recurrence should always be considered in the studies assessing therapeutic efficacy in CD.